Prescribing patterns of antibiotics among elderly patients in Outpatient Department of Hospital Sultanah Nur Zabirah (HSNZ) - Najamin, lzzatie Iwanie; Mat Kia, Nurul Hidayah; Ismail, Siti Nor Amira (2018)
Aim: To study the prescribing patterns of antibiotics among elderly patients in outpatient department of Hospital Sultanah Nur Zahirah (HSNZ). Methods: A retrospective study was done at outpatient department of Hospital Sultanah Nur Zahirah (HSNZ) during six month period. A total of 234 prescriptions were selected. Elderly patients from 60 years old and above which prescribed single or combination of antibiotics were included. The data of the drug and patients characteristics that obtained from the prescription were computed by using Microsoft Excel. Then the data were analysed by using SPSS 22. Results: In this study 234 prescriptions were screened. For the number of antibiotics prescribed per prescription, 94.4% of the prescriptions contained only one antibiotic prescribed. 88.9% of the prescribed antibiotics were rational. Duration of administration was the common type of irrationality found among the irrational prescriptions. The average of duration of prescription was 18.25 days. The top most frequent prescribed antibiotics were chloramphenicol which consists 91 (38.9%). Out of the 234 patients, 83 (35.5%) patients were prescribed with antibiotics for cataract complication. Conclusion: The most frequent prescribed antibiotics among the elderly patients from outpatients department of Hospital Sultanah Nur Zahirah were chloramphenicol. The antibiotic of chloramphenicol was indicated for cataract, which was highest percentage of all other infection that prescribed with antibiotics. Most of the prescribed antibiotics were found to be rational. Thus, this study concludes that the prescribing of antibiotics in this hospital is rational according to the National Antibiotic Guidelines 2014.